The Power to Tax in Sub-Saharan Africa: LTUs, VATs, and SARAs - Christian Ebeke; Mario Mansour; Grégoire Rota-Graziosi (Fondation pour les études et recherches sur le développement international (FERDI), 2016)
In the context of achieving the new Sustainable Development Goals, revenue mobilization is a high priority in developing countries and in Sub-Saharan Africa, where governments' ability to tax remains limited. Using a unique revenue dataset spanning the period 1980-2010, we analyze three important tax reforms: the Large Taxpayers Unit (LTU), the Value Added Tax (VAT), and the Semi-Autonomous Revenue Agency (SARA). We propose an ex-post impact assessment of these tax reforms in SSA countries based on propensity-score matching methodology (PSM) and synthetic control method (SCM). VAT and SARA are found to have an unambiguously large and positive effect on non-resource taxes, while the impact of LTU is insignificant—LTU seems however an important precondition for the adoption of the first two reforms. We conclude also that VAT and SARA display some synergy, and their positive effects strengthen several years after their adoption.Keywords: tax reforms; Africa; revenue mobilization; causality.
Keywords: H2; O23; O55; C1; 330; tax reforms; Africa; revenue mobilization; causality.